2008
DOI: 10.1515/cclm.2008.161
|View full text |Cite
|
Sign up to set email alerts
|

Gender-modulated impact of apolipoprotein A5 gene (APOA5) −1131T>C and c.56C>G polymorphisms on lipids, dyslipidemia and metabolic syndrome in Turkish adults

Abstract: Excess risk for low HDL-C, dyslipidemia and MS is associated with the rare alleles of the APOA5 SNPs and non-carriers of common haplotype in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 29 publications
2
39
1
Order By: Relevance
“…The SNP rs662799 has a much higher MAF in Chinese populations (26.7% in Han Chinese in HapMap, 28.8% in the Hong Kong subjects and 29.3% in the Guangzhou subjects) compared to Caucasians (5-8%) and Turks (12.8%). [33][34][35] Our results should prompt the search for SNPs that occur commonly in other ethnic populations and influence triglycerides to a similar extent. At the same time, we have yet to analyze SNPs that are uncommon in Chinese and Female gender, systolic blood pressure, current smoking, alcohol drinking, hypertension, diabetes, rprimary education and Ztertiary education were allowed to enter into the regression models, but were all excluded.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The SNP rs662799 has a much higher MAF in Chinese populations (26.7% in Han Chinese in HapMap, 28.8% in the Hong Kong subjects and 29.3% in the Guangzhou subjects) compared to Caucasians (5-8%) and Turks (12.8%). [33][34][35] Our results should prompt the search for SNPs that occur commonly in other ethnic populations and influence triglycerides to a similar extent. At the same time, we have yet to analyze SNPs that are uncommon in Chinese and Female gender, systolic blood pressure, current smoking, alcohol drinking, hypertension, diabetes, rprimary education and Ztertiary education were allowed to enter into the regression models, but were all excluded.…”
Section: Discussionmentioning
confidence: 72%
“…A previous study in Caucasians showed a stronger association of rs662799 with plasma triglycerides in men, 3 but a study in Turkey showed that the association of the APOA5 genetic variants with plasma triglycerides and the metabolic syndrome was more significant in women than in men. 35 This may be another example of a sex difference in the contribution of an SNP to a phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In a Singaporean population, both male and female carriers of the C allele of APOA5- 1131T>C had higher TG levels [40]. In another study, no such association was found in a middle-aged and elderly Turkish male population [41]. It is well established that a HC/LF diet can induce HTG [11].…”
Section: Discussionmentioning
confidence: 99%
“…Because the articles by Grallert et al (2007) and Ong et al (2011) included two separate groups, respectively, these groups were considered as two independent studies. Finally, 12 studies from 10 articles (Grallert et al, 2007;Yamada et al, 2007;Dallongeville et al, 2008;Hsu et al, 2008;Komurcu-Bayrak et al, 2008;Mattei et al, 2009;Kisfali et al, 2010;Niculescu et al, 2010;Ong et al, 2011;Vasilopoulos et al, 2011) were included in our meta-analysis. Among 10 publications, only Ong' study (Ong et al, 2011) Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…As higher triglyceride is one crucial risk factor in the development of many diseases, including MetS, the polymorphism of the ApoA5 gene may be involved in MetS. Indeed, several studies in different populations have found the association between the ApoA5 polymorphism and the risk of MetS (Grallert et al, 2007;Yamada et al, 2007;Dallongeville et al, 2008;Hsu et al, 2008;Komurcu-Bayrak et al, 2008;Mattei et al, 2009;Kisfali et al, 2010;Niculescu et al, 2010;Ong et al, 2011;Vasilopoulos et al, 2011). However, these results are not quite consistent; therefore, we conducted a meta-analysis to clarify the exact association between the ApoA5 polymorphism and the risk of MetS.…”
Section: Introductionmentioning
confidence: 99%